Risk Management Analysis and Business Opportunity Identification in Sharia Investment Development - Ahmad Muhajir; Pani Akhiruddin Siregar; Ahmad Afandi Surbakti (Takaza Innovatix Labs Ltd., 2025)
This article explores the role of risk management and business opportunity mapping in enhancing the development of Sharia-compliant investments, drawing on recent studies discussing Islamic investment concepts, risk control mechanisms, investor behavior, and the evolution of the halal industry. Sharia-based investments possess distinct characteristics due to their obligation to comply with Islamic principles, including the prohibition of riba, gharar, and maysir. As a result, the risks involved extend beyond financial aspects to include Sharia compliance risks. Based on a comprehensive literature review of nationally indexed journals, this study identifies various types of risks such as market, liquidity, operational, credit, and Sharia compliance risks, along with management strategies including prudential assessment, portfolio diversification, strengthened Sharia governance, and the use of digital technologies. The article also highlights emerging business opportunities within the Islamic investment landscape, particularly in the halal industry, Islamic fintech, sukuk instruments, Sharia mutual funds, and Sharia-based financing schemes. The findings indicate that strengthening risk mitigation strategies while optimizing business opportunities can support sustainable growth in Sharia investment. This study contributes academically to the understanding of Islamic investment dynamics and serves as a practical reference for investors and Islamic financial institutions.